Life Satisfaction of University Students in Relation to Family and Food in a Developing Country - Schnettler, Berta; Miranda-Zapata, Edgardo; Grunert, Klaus G.; Lobos, Germán; Denegri, Marianela; Hueche, Clementina; Poblete, Héctor (Frontiers in Psychology, 2017)
Life satisfaction and satisfaction with food-related life are associated with healthy eating habits, family interaction around eating and family support. The present study evaluates the relationship between satisfaction with food-related life and satisfaction with family life, and their relationship with life satisfaction in university students. We identify the relationship of two different types of family support and student satisfaction with family life and explore a moderator effect of gender. A questionnaire was applied to a non-probabilistic sample of 370 students of both genders (mean age 21 years) in Chile, including Satisfaction with Life Scale (SWLS), Satisfaction with Food-related Life (SWFoL) scale, Satisfaction with Family Life (SWFaL) scale and the Family Resources Scale (FRS). Using structural equation modelling, we found that students’ life satisfaction was related to satisfaction with family life and food-related life. A high positive relationship was identified between intangible family support and students’ satisfaction with family life, which would have a mediating role between intangible support and life satisfaction. Using multi-group analysis, a moderator effect of gender was not found. These findings suggest that improving satisfaction with food-related life, satisfaction with family life and intangible family support is important for both female and male students.